(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Elena V. Lopanova (Khimki, Russian Federation) The article deals with the ways of generalizations and improvement military students’ vocabulary. The most effective methods and techniques for enriching the vocabulary with special words in the process of teaching the Russian language and the culture of business communication are described. The necessity for military students to observe the lexical norm is underlined. It is concluded that the enrichment of the vocabulary of military students should be of a systematic nature and should be based on a communicative approach. Key words: military students, EMERCOM of Russia, vocabulary, special words, terms, communicative approach.